(NpOWESTI(B, (NRASSKAZY I FELXETONY(B: [1840-1861] / s (N~ASTX (B5s - (NnEKRASOW(B, (NnIKOLAJ aLEKSEEWI^s ((NmOSKWA(B: s (NhUDOVESTWENNAQ LITERATURA(B, s, 1966)
(Nw PQTYJ TOM WO[LI POWESTI(B, (NRASSKAZY I FELXETONY (B1840-1861 (NGG(B.s
rus
Keywords: (NpOWESTX(B, (NRASSKAZYs; (NfELXETONYs